Step
*
1
1
1
2
of Lemma
iterate-rotate-rotate-by
.....subterm..... T:t
3:n
1. n : ℕ
2. i : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i - 1 = rotate-by(n;i - 1) ∈ (ℕn ⟶ ℕn)
6. x : ℕn
7. ((x + (i - 1) rem n) + (1 rem n) rem n) = ((x + (i - 1)) + 1 rem n) ∈ ℤ
⊢ (x + i rem n) = ((x + (i - 1)) + 1 rem n) ∈ ℤ
BY
{ (EqCDA THEN Auto) }
Latex:
Latex:
.....subterm.....  T:t
3:n
1.  n  :  \mBbbN{}
2.  i  :  \mBbbZ{}
3.  \mneg{}i  <  1
4.  0  <  i
5.  rot(n)\^{}i  -  1  =  rotate-by(n;i  -  1)
6.  x  :  \mBbbN{}n
7.  ((x  +  (i  -  1)  rem  n)  +  (1  rem  n)  rem  n)  =  ((x  +  (i  -  1))  +  1  rem  n)
\mvdash{}  (x  +  i  rem  n)  =  ((x  +  (i  -  1))  +  1  rem  n)
By
Latex:
(EqCDA  THEN  Auto)
Home
Index